PERENCANAAN PEMBANGUNAN DESA DALAM PERSPEKTIF PERATURAN PEMERINTAH NOMOR 72 TAHUN 2005 TENTANG DESA - Atikalani, Mrs. (FIA UB, 2012)
Aspects of sustainability of development activities is very important to note because it concerns the problem: (a) development carried out by both central and local governments do not reflect the optimal level of local empowerment. Development carried out sometimes incompatible or inconsistent with the actual needs of society.(b) Movement of autonomy and decentralization in the end result of Government Regulation Number 72 Year 2005 on the Village that regulate more about planning at the village level. For example in artide 63 paragraph 1 of Regulation No. 72 of 2005 states that: In terms of village government as a rural development plan created the unit in the planning of the district / city and in paragraph 2 that: Planning of rural development as referred to in paragraph (1) prepared in a participatory manner by the village administration in accordance with their authority. These two verses show the level down to village level planning and participatory. The next chapter then describes the five-year term and annual planning.(c) an interesting fact that occurred in the South Barito district showed that the complexity of the determinants of the success of village planning,the readiness of forces to support infrastructure andfacilities is also greatly affect the success of the plan making village. Result of the research indicates that the creationon village development planning has shown the existence of a good process and is done in aparticipatory manner, as mandated in Government Regulation No. 72 of 2005. Although there are still some villages that have not been able to prepare villages plans. The are several factors the affect rural development planning, among others : Supporting factors : a) Community participation; b) Has been appointed village planning facilitator maker. In hibitting factors : a) The ability of village official; b) Managerial ability village government; c) Lack of facilities and infrastructure supporting the village government; d)Weak regulatory agencies as regional policy maker